Predictors of an unfavorable course of COVID-19 - V. Ya. Polyakov; Yu. A. Nikolaev; Zh. A. Garina; I. M. Mitrofanov; E. V. Sevostyanova (Сибирский научный медицинский журнал, 2023)
The aim of the study was to identify the features of the unfavorable clinical course of a new coronavirus infection.Material and methods. The analysis of clinical data, laboratory results and comorbidity of 168 patients with a confirmed diagnosis of a new coronavirus infection aged 65,0 [57,0; 74,0] years was carried out. Two groups of patients were distinguished – 126 persons with a moderate course and with clinical recovery in the outcome of the disease and 42 persons with a severe course and a fatal outcome of the disease. Transnosological polymorbidity was assessed by the average number of nosologies corresponding to the three-digit ICD-10 rubricification, transsystemic – by the number of affected systems. Hemogram parameters, blood content of C-reactive protein, creatinine, urea, glucose, prothrombin index, international normalized ratio, activated partial thromboplastin time, platelet count, D-dimer concentration were estimated.Results. In the group of patients with fatal outcomes, compared to patients with recovery, there were statistically significantly higher indices of transnosological and transsystemic polymorbidity (1.5 and 2 times, respectively), they were more likely to have ischaemic heart disease, myocardial infarction, transient ischemic attack in anamnesis, atrial fibrillation, chronic heart failure; blood concentration of C-reactive protein, fasting glucose, urea, D-dimer in the blood serum was higher, the number of thrombocytes was less.Conclusions. A high degree of transnosological and transsystemic polymorbidity, a history of myocardial infarction and transient ischemic attack, comorbid chronic heart failure, atrial fibrillation, an increase in D-dimer, CRP content, and a decrease in platelet number are predictors of severe course and the lethal outcome of COVID-19.